Study of Bed Deformation Trend of Wakouzi-Majiazui Section in the Upper Jingjiang Reach of Yangtze River - ZHANG Hong; LIU Qihang (Renmin Zhujiang)
The riverbed scour and deposition of sandy section in Jingjiang reach of Yangtze River deforms dramatically since the operation of the Three Georges Reservoir.Taking the Wakouzi-Majiazui section as the example,based on recent channel topography and hydrological data,this paper simulates and predicts the bed deformation trend of the section for the next 20 years through a two-dimensional flow-sediment numerical model.The results indicate that:The river regime of Wakouzi-Majiazui section is generally stable for the next 20 years,and the main channel erosion will continue and develop downstream.The Jincheng sandbar shows no significantly variation,and the evolution of Tuqi sandbar is characterized by the sedimentation of left branch and scouring of right branch,with the right branch in dominant position continuously,which offer an important reference for channel and waterway regulation.